The art of mapping IoT devices in networks. Issue 4 (April 2018) - Bajpai, Pranshu; Sood, Aditya K; Enbody, Richard J
Abstract : Improperly secured Internet of Things (IoT) devices have been commandeered by bot herders and other malicious attackers. Organisations need a way to identify and track these IoT devices, which are often brought in unofficially by users. But network administrators face a number of challenges in tracking IoT devices across their organisation. Improperly secured Internet of Things (IoT) devices have been exploited by bot herders and other malicious attackers. So organisations need a way to identify and track these devices. Pranshu Bajpai, Aditya Sood and Richard J Enbody look at the difficulty of defining identifying characteristics of IoT devices due to their immensely diverse nature. They offer a model to identify IoT devices in networks using a variety of scanning techniques and they discuss the pros and cons of discovery techniques, presenting results from actual scans.